The concentration-effect relationship of quinine-induced hearing impairment - Paintaud, G; Alván, G; Berninger, E; Gustafsson, L L; Idrizbegovic, E; Karlsson, K K; Wakelkamp, M (Clinical pharmacology and therapeutics, 1994)
Quinine-induced reversible hearing impairment at the frequencies of 1000 and 2000 Hz was investigated in healthy volunteers to analyze the plasma concentration-effect relationship of the drug. Six subjects were given two identical oral doses of quinine and a constant rate infusion of quinine over 6 hours (15 mg.kg-1) on three separate occasions. A simple pharmacodynamic model, E = k.C gamma (in which E is effect, k is a proportionality constant, C is drug concentration, and the exponent gamma is a fitting parameter), was found to describe well the relationship between hearing impairment and quinine concentrations in a hypothetical effect compartment. No statistical differences were found in the estimated parameters when the three dosings were compared, indicating that quinine-induced hearing impairment is independent of route of administration. The first-order rate constant (keo), linking plasma concentrations to the concentrations in the effect compartment, was (mean +/- SD) 0.71 +/- 0.19 and 0.99 +/- 0.37 hr-1 for 1000 and 2000 Hz, respectively. The corresponding values of k were 0.15 +/- 0.10 and 0.12 +/- 0.19 and the values of gamma were 2.13 +/- 0.57 and 3.44 +/- 1.04 for 1000 and 2000 Hz, respectively. Effect was also analyzed by semiparametric pharmacodynamic modeling, which gave results comparable to those obtained with the link model. We conclude that a simple power function is a reliable pharmacodynamic model for describing quinine-induced hearing impairment in healthy subjects.